2002
DOI: 10.1002/ccd.3050
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Palmaz stent renal artery stenosis revascularization registry report: Four‐year follow‐up of 1,058 successful patients

Abstract: Palmaz-Schatz stent revascularization of renal artery stenosis was successfully performed on 1,058 patients who were entered into a voluntary, multicenter registry. The revascularization procedures were performed because of poorly controlled hypertension, preservation of renal function, and congestive heart failure. All 1,058 patients were eligible for > or =6-month clinical follow-up, which focused on subsequent renal function, blood pressure, number of antihypertensive medications, and survival. At 4-year fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
5
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(92 citation statements)
references
References 35 publications
6
79
5
2
Order By: Relevance
“…Moreover, earlier studies included patients with moderate diameter stenoses (50% to 70%) that are unlikely to cause hemodynamic compromise. 14 -19,21-24,28,29,35 With an adequate sample size, improvement of renal function was found that was similar to that reported by van de Ven et al, 19 Iannone et al, 20 and Dorros et al 21,22 The choice of stent-supported angioplasty as treatment modality may have contributed to the beneficial outcome in the study. We were able to reduce the renin-angiotensin system to Ͻ30% in all cases.…”
Section: Zeller Et Al Functional Responses To Renal Artery Stenting 2247supporting
confidence: 67%
“…Moreover, earlier studies included patients with moderate diameter stenoses (50% to 70%) that are unlikely to cause hemodynamic compromise. 14 -19,21-24,28,29,35 With an adequate sample size, improvement of renal function was found that was similar to that reported by van de Ven et al, 19 Iannone et al, 20 and Dorros et al 21,22 The choice of stent-supported angioplasty as treatment modality may have contributed to the beneficial outcome in the study. We were able to reduce the renin-angiotensin system to Ͻ30% in all cases.…”
Section: Zeller Et Al Functional Responses To Renal Artery Stenting 2247supporting
confidence: 67%
“…Many of the renal functional outcomes of these series are summarized elsewhere (49,50). It should be emphasized that recent small, prospective trials of renal angioplasty (mostly without stents) in selected patients produced only modest improvements in BP (51)(52)(53).…”
Section: When To Pursue Renal Revascularization For Ischemic Nephropathymentioning
confidence: 99%
“…Evidence was weak owing to sparseness of data or disagreement among studies on other baseline factors and outcomes (Table 4), including the presence of bilateral disease among patients having revascularization (25,27,34,37,39,40,45) or among those enrolled in natural history studies (55,56); the degree of kidney function (20,51) No study that met eligibility criteria reported analyses of whether periprocedural interventions, such as different …”
Section: Adverse Events and Restenosis Ratesmentioning
confidence: 99%